2000
DOI: 10.1074/jbc.m003615200
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Protein Kinase C on the Levels of Epithelial Na+ Channel Subunit Proteins

Abstract: Regulation of epithelial Na؉ channel (ENaC) subunit levels by protein kinase C (PKC) was investigated in A6 cells. PKC activation altered ENaC subunit levels, differentially decreasing the levels of both ␤ and ␥, but not ␣ENaC. Temporal regulation of ␤ and ␥ENaC by PKC differed; ␥ENaC decreased with a time constant of 3.7 ؎ 1.0 h, whereas ␤ENaC decreased in 13.9 ؎ 3.0 h. Activation of PKC also resulted in a decrease in trans-epithelial Na ؉ reabsorption for up to 48 h. PMA activation of PKC resulted in negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 21 publications
5
78
2
Order By: Relevance
“…P2Y receptors (the main targets of UTP) are G protein-coupled and act via the inositol phosphate pathway to stimulate Ca 21 release from intracellular stores, but can also act via multiple secondary signal transduction pathways, including protein kinase C (PKC) (36). Activation of PKC has been shown to reduce ENaC activity and modify its subunit composition (37,38). Our previous data indicate that infection of mice with RSV results in activation of PKCz as indicated by its phosphorylation and translocation from the cytoplasm to the plasma membrane (27).…”
Section: Discussionmentioning
confidence: 99%
“…P2Y receptors (the main targets of UTP) are G protein-coupled and act via the inositol phosphate pathway to stimulate Ca 21 release from intracellular stores, but can also act via multiple secondary signal transduction pathways, including protein kinase C (PKC) (36). Activation of PKC has been shown to reduce ENaC activity and modify its subunit composition (37,38). Our previous data indicate that infection of mice with RSV results in activation of PKCz as indicated by its phosphorylation and translocation from the cytoplasm to the plasma membrane (27).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that activation of PLC signaling inhibits ENaC activity either by activating PKC or depletion of the inner membrane PI(4,5)P 2 content (Kunzelmann et al, 2005). The activation of PKC is known to evoke later response and to maintain long-term (up to 48 h) downregulation of ENaC by decreasing plasma membrane levels of the channel (Stockand et al, 2000;Booth and Stockand, 2003). The level of ␥-ENaC decreased by PKC with a time constant of 3.7 h, and the level of ␤-ENaC decreased in 13.9 h. The fact that treatment of tissues with 2-APB, a cell-permeable antagonist of inositol trisphosphate (IP 3 ) receptor and store-operated channels (Bootman et al, 2002), did not affect UTP effect on ENaC activity suggests that the involvement of the second branch of the PLC pathway (IP 3 production) in response to UTP is negligible.…”
Section: Mechanism Of P2y 4 -Mediated Inhibition Of Amiloridesensitivmentioning
confidence: 99%
“…During this phase, there is a clear increase in the amount of ENaC protein within the cell, as well as at the apical membrane (100, 107, 189). However, controversy surrounds which subunits of the heteromultimeric ENaC are induced by aldosterone, with some studies showing increases in ␣-ENaC levels (100,107,110,114) and some increases in ␤-ENaC levels (158,189), and yet others reporting increases in both (42, 47). Moreover, controversy surrounds the idea that expression and insertion into the apical membrane of ENaC subunits are discordantly and independently regulated by aldosterone (67,100,107,139,189).…”
Section: Temporal Actions Of Aldosteronementioning
confidence: 99%